Strategi Model Bisnis UMKM Kuliner untuk Bertahan di Era COVID-19 - Richa Nahdalaily Fathara; Muhamad Rizal; Ria Arifianti; Asmaul Husna (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2021)
The purpose of this study is to describe the business model innovation with the Business Model Canvas approach that can be applied to MSMEs during the COVID-19 pandemic so that MSMEs can survive (business resilience). This research uses a qualitative method, with literature studies accessed from several sources, both print and electronic media, books, and research results from various electronic journals. The data analysis used is descriptive analysis. The description of the business model innovation is presented using the Business Model Canvas (BMC) tools. The nine blocks of BMC are important elements that must be thoroughly analyzed in detail in order to achieve business resilience. A business model strategy is needed in achieving business goals and developing SME products so that they are more competitive and can survive in the pandemic era. The use of the right business model will result in MSMEs being able to achieve business resilience.